Development of Website-Based Interactive Multimedia on Cell Material to Improve Critical Thinking Skills and Learning Independence of Class XI High School Students - Sari*, Yenni Novita; Yulianti, Evy; Kurniawati, Atik; Huang, Tzou-Chi (Jurnal Pendidikan Sains Indonesia, 2024)
The challenges faced in teaching cell material in high school show the need for innovation in learning media to facilitate understanding and increase students' learning motivation. This study aims to develop website-based interactive multimedia on cell material and evaluate the media's feasibility, practicality, and effectiveness in improving critical thinking skills (CTS) and learning independence of grade XI students of SMAN 1 Ngemplak. This type of research is research and development (R D) using the ADDIE model by Dick and Carey, including the stages of analysis, design, development, implementation, and evaluation. Field trials were conducted by a quasi-experimental method using a non-equivalent control-group pretest-posttest design. 62 students from two classes XI of SMA Negeri 1 Ngemplak became field trial subjects, divided into control classes (31 students) and experimental classes (31 students) by applying cluster random sampling techniques. Data on CTS and learning independence were measured using test and non-test techniques and then analyzed using t-tests. The results showed that: 1) website-based interactive multimedia is feasible to be used in the learning process, 2) website-based interactive multimedia is practical to use in the learning process, and 3) website-based interactive multimedia is effective in improving students' CTS and learning independence